Utilisation of readily available information and communication technologies in cattle management in Kgatleng and south east districts in Botswana - Mooketsi, Bojelo Esther (Department of Computer Science, 2024)
In this dissertation, the researcher uses survey research to develop and understanding of cattle management in some areas in Botswana and how the Bolus and Livestock Identification and Traceback System (LITS) database can be used to enhance it.